Impact of hypercapnia on alveolar Na+-transport : Establishing a system for ENaC-protein detection - Buchbinder, Benno Andreas; Justus Liebig University Giessen (My University, 2013)
Acute respiratory distress syndrome is a life threatening condition triggered by a variety ofpulmonary and extrapulmonary causes, that is characterized by pulmonary edema andsubsequently impaired gas exchange. Due to lung protective ventilation strategies, itstreatment is often associated with systemic accumulation of CO2, a condition termedpermissive hypercapnia. Recent studies report a negative effect of CO2 on alveolar fluidclearance, a process mediated by its two key elements the Na+,K+-ATPase and epithelialNa+-channels (ENaCs). A reduced activity of the Na+,K+-ATPase during hypercapnia hasalready been demonstrated, but regulation of ENaC has never been directly linked to CO2.Many molecular signaling events that are activated during hypercapnia are known toregulate ENaC function, so the present study aimed to generate and subsequently applytechniques to investigate a possible contribution of ENaC to the reduction of alveolarepithelial fluid transport upon hypercapnia.ENaC function was studied in H441 cells by Ussing chamber experiments which revealedno significant regulation during short term hypercapnia, but a clear reduction of ENaCfunction during sustained hypercapnia.To identify the signaling mechanism on the molecular level, epitope-tagged human ENaCconstructs for the α-, β- and γ-subunit were cloned and initially expressed in A549 cells.Exposition to hypercapnia up to 4 hours did not significantly reduce cell surface expressionof the ENaC-subunits, but after 24 hours, a significant decrease of β-ENaC was observed.Since the molecular sizes of α- and γ-ENaC expressed in A549 cells were differing frompreviously published studies, transfection of ENaC was continued in other cells. H441 cellsare commonly used for ENaC studies, so their transfection was established, yielding anefficiency of about 60 %. The molecular sizes of transfected ENaC subunits matched thepattern that was expected, but expression levels were evanescent and too low for furtherexperiments. Since ENaC detection in these two cell lines remained problematic, a novelmethodology was applied. Since the primary site of ENaC expression in the lung areepithelial cells, rat primary alveolar epithelial cells type II were used as recipients forENaC plasmids. Non-viral transfection of ATII cells has been inefficient in the past, butduring the present study a protocol was generated to efficiently deliver nucleic acids toexactly this cell type. ENaC expression was largely increased in ATII cells, compared tothe cell lines used, indicating that established system might be extremely useful for furtherstudies involving ENaC turnover.Thus, a new and highly relevant, non-viral transfection technique for primary alveolarepithelial type II cells was established, providing ground-breaking opportunities for futurepulmonary research.

Das Atemnotsyndrom des Erwachsenen ist eine lebensbedrohliche Erkrankung, ausgelöstdurch eine Reihe von Faktoren, die direkt oder indirekt auf die Lunge einwirken .Charakteristisch für dieses Syndrom sind pulmonare Ödeme und daraus resultierend eineingeschränkter Gasaustausch. Die daher benötigte künstliche Beatmung führt im Zugevon protektiven Beatmungsstrategien oft zu einer systemischen Anreicherung von CO2(Hyperkapnie). Einige Studien zeigen, dass erhöhte CO2-Level den Flüssigkeitstransportder Lunge einschränken. Dieser aktive Prozess wird maßgeblich durch zwei Komponenten,die Na+,K+-ATPase und epitheliale Na+-Kanäle (ENaCs), kontrolliert. EineBeeinträchtigung der Na+,K+-ATPase durch CO2 gezeigt, für ENaCs ist dies bislang nichtbekannt. Einige bekannte Regulatoren von ENaCs werden jedoch während Hyperkapnieaktiviert. Das Ziel der vorliegenden Arbeit war, Methoden zu etablieren und anzuwenden,die einen möglichen Einfluss von CO2 auf ENaC zeigen.Funktionelle Versuche wurden an H441-Zellen mit Ussing-Kammer-Messungendurchgeführt. Während akuter Hyperkapnie konnte keine signifikante Regulation vonENaC nachgewiesen werden, jedoch war die ENaC-Funktion bei anhaltender Hyperkapniedeutlich verringert.Um die Signalwege auf molekularer Ebene zu untersuchen, wurde die α-, β- und γ-Untereinheit des humanen ENaC kloniert, genetisch modifiziert und in A549 Zellenüberexprimiert. Nach bis zu vierstündiger Hyperkapnie erfolgte keine Regulation vonENaC, jedoch wurde nach 24 Stunden eine deutlich verminderte Menge β-ENaC in derZellmembran nachgewiesen. Da die Größen von α- und γ-ENaC von den bisherpublizierten abwichen, wurden weitere Versuche in H441 Zellen durchgeführt. DieTransfektion dieser Zelllinie wurde etabliert und erreichte eine Effizienz von ungefähr 60%. Die posttranslationale Regulation der α- und γ-Untereinheiten, insbesondere dieproteolytische Aktivierung funktionierten wie in der Literatur beschrieben, jedoch warendie Expressionslevel zu gering für weitere Versuche. In der Lunge werden ENaCsüberwiegend in epithelialen Zellen exprimiert. Diese Zellen konnten bisher jedoch nichteffizient transfiziert werden, ohne Viren einzusetzen. In der vorliegenden Arbeit wurdejedoch eine effiziente Methode zur Transfektion von primären epithelialen Zellen der Ratteerarbeitet. Die Expression von transfizierten ENaC-Untereinheiten war in diesen Zellendeutlich erhöht, weswegen die Etablierung dieses Systems ausschlaggebend für weitereVersuche ist.Die vorliegende Arbeit beschreibt daher zum ersten Mal die nicht-virale, effizienteTransfektion von primären alveolaren Zellen und liefert damit ein bedeutendes neuesWerkzeug für die Lungenforschung.
Einfluß von Hyperkapnie auf den alveolaren Na+-Transport : Etablierung eines Systems zur Detektion von ENaC-Proteinen
Keywords: Hyperkapnie; ENaC; Nucleofection; Primärzellen; Hypercapnia; ENaC; Nucleofection; ATII cells; ddc:570